2013
DOI: 10.1063/1.4774336
|View full text |Cite
|
Sign up to set email alerts
|

Vortical control of forced two-dimensional turbulence

Abstract: A new numerical technique for the simulation of forced two-dimensional turbulence [D. Dritschel and J. Fontane, “The combined Lagrangian advection method,” J. Comput. Phys. 229, 5408–5417 (2010)10.1016/j.jcp.2010.03.048] is used to examine the validity of Kraichnan-Batchelor scaling laws at higher Reynolds number than previously accessible with classical pseudo-spectral methods, making use of large simulation ensembles to allow a detailed consideration of the inverse cascade in a quasi-steady state. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…In the regime with forward enstrophy transfer, the energy spectrum is typically steeper than k −3 , both in numerical simulations [32] and in experiments [33]. Moreover, Scott [34], Fontane et al [35] report some deviations from the theoretical predictions of Kraichnan [22]. Pandit et al [36] describe properties of 2D flows in the presence of complex forces.…”
Section: Introductionmentioning
confidence: 99%
“…In the regime with forward enstrophy transfer, the energy spectrum is typically steeper than k −3 , both in numerical simulations [32] and in experiments [33]. Moreover, Scott [34], Fontane et al [35] report some deviations from the theoretical predictions of Kraichnan [22]. Pandit et al [36] describe properties of 2D flows in the presence of complex forces.…”
Section: Introductionmentioning
confidence: 99%
“…In this case strong, nearly-circular coherent vortices can again be unambiguously distinguished from the weak filamentary background flow 6,7,10,[21][22][23][24] . by Kraichnan 9 , and this range extends to larger scales as the minimum allowed distance to vortices increases, as is evident from examining the middle and lower sets of black curves in figure 3b: these spectra correspond, from top to bottom, to increasing minimum distances to vortices.…”
Section: Dmentioning
confidence: 85%
“…by Kraichnan 9 , and this range extends to larger scales as the minimum allowed distance to vortices increases, as is evident from examining the middle and lower sets of black curves in figure 3b: these spectra correspond, from top to bottom, to increasing minimum distances to vortices. Similarly, Fontane et al 6 found E(k) ∼ k −2 for the entire vorticity field, but…”
Section: Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The fate of random initial vorticity distributions on a sphere complex vorticity distributions and in doubly periodic or spherical domains this clean scaling law has been questioned (Fontane, Dritschel & Scott 2013). When the viscosity is reduced little by little (i.e.…”
Section: Overviewmentioning
confidence: 99%